Epidemiological profile of COVID-19 patients admitted in Palakkad district- a descriptive study - Zachariah, Shilu M.; Chakkanmattil, Sreedevi; Nallat, Divyamol; Soman, Deepak K. (International Journal Of Community Medicine And Public Health, 2022)
Background: The World Health Organization (WHO) declared coronavirus disease 2019 (COVID-19) a public health emergency of international concern. There is paucity of published data from India especially regarding the epidemiological information of COVID-19 patients and factors affecting the length of hospitalization. Methods: The objectives of the study are to determine the epidemiological profile of COVID-19 patients and to determine the factors associated with their duration of hospital stay. The study is a descriptive study which includes all COVID-19 patients admitted to COVID-19 treatment centres of Palakkad district from 23 May 2020 to 30 June 2020. Results: A total of 467 patients were obtained constituting 362 (77.5%) males and 105 (22.5%) females. The mean age was 36.52±14.44 years. 84 (17.99%) patients had comorbidities and 53 (11.35%) were symptomatic. The mean duration of hospital stay was 13.00±5.79 days (IQR 9-15). Symptomatic patients had higher odds of having a longer hospitalization compared to asymptomatic patients and this was found to be highly significant. Presence of comorbidities was also associated with longer duration of hospital stay which was significant. Conclusions: A knowledge about the length of hospital stay will be crucial in determining the necessary infrastructure and manpower to manage the COVID-19 patients. If careful planning of health resources allocation is done, it will prevent undue overburdening of the health systems especially during a surge of COVID-19 cases.